The Problem of Understanding – Explanation and Inner Contradictions of Culture - Rubavičius, Vytautas (Problemos, 1984)
In the article the attention is focused on the relationship between the opposition of the methods of understanding-explanation (the tradition of hermeneutics) and the explanation of inner contradictions in culture. The attempts of representatives of modem philosophical hermeneutics to unify methods of understanding are being analysed. The conclusion is drawn about the impossibility to create essentially different methodologies of sciences. Consequently, the differences between the humanitarian and scientific fields of culture must not be made absolute. The author maintains that the contradictions of culture should be analysed on the basis of the theory of action.